A new genus of Staphylinina and a review of major lineages (Staphylinidae: Staphylininae: Staphylinini). Issue 8 (17th November 2019) - Brunke, Adam J.; Smetana, Aleš
Abstract : Despite their familiarity to most naturalists, the large rove beetles of the subtribe Staphylinina are poorly understood systematically and have never been the subject of a focused phylogenetic analysis. Within a total evidence analytical framework, an unusual Staphylinina from China was demonstrated to be the sister group of Ontholestes and was described as Lesonthotes vulneratus Smetana and Brunke, gen. et sp. nov. Based on these results, Ontholestes was morphologically redefined and the Cingulatus group of species was established. The Neotropical genus Leistotrophus was resolved as a member of Ontholestes, within the latter clade but synonymy was avoided until molecular data are available for the former. Ontholestes lowi Rougemont, 2016 syn. nov. is proposed as a junior synonym of Ontholestes borneensis Cameron, 1942. We also confirmed the existence of and morphologically defined three major lineages within Staphylinina, of which two were previously based on molecular data only. This study builds on previous work by Smetana and Davies (2000 ) and lays the framework for more extensive analysis of the subtribe. Our results emphasize the continued value of morphological characters in a total evidence framework for resolving the systematics of charismatic but poorly explored groups. www.zoobank.org/urn:lsid:zoobank.org:pub:776F033D-4556-483C-8725-707E1B02C040